The adhesion of Portugal to the gold standard : the debate at the chamber of deputies - Mendonça, António (2022)
Gold Standard was introduced in Portugal by the "Letter of Law" of July 29, 1854, and lasted until July 9, 1891. Portugal was the second country to adopt this monetary regime in Europe, after England where it ruled since 1816, anticipating with this measure the majority of the developed countries of the time for more than twenty years. The decision of the Portuguese govemment was based upon various reasons, in an apparently unfavourable background, where the discoveries of new gold mines in California and Australia were making pressure for the devaluation of this metal against silver. The aim of the paper is to present the debate engaged at the Chamber of Deputies that lasted for almost three weeks and involved around twenty people, and reflects itself on almost 170 pages ofthe Joumal ofthe Chamber. The paper tries, on the first place, to identify the main differences between the proposals of the majority represented by the govemment and the Commission of Finance ofthe Chamber ofDeputies and those ofthe opposition represented by the former Minister of Finance, António José Ávila. Secondly it tries to express the arguments presented by both sides and, simultaneously, to establish the connections with the schools of economic thought of the time. Lastly it tries to conclude in which extent the final Letter of Law reflects the way the discussion was held.